Ethnomathematics In Action: Leveraging Traditional Congklak For Meaningful Mathematics Learning - Mulyadi, Magdalena; Putra, Harry Dwi (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
Mathematics, often perceived as abstract and daunting, can be made more engaging and relevant through its integration with cultural contexts. Ethnomathematics, the study of mathematics embedded in cultural practices, offers a promising approach to enhance student motivation and understanding. This study investigates the potential of the traditional Indonesian Congklak game to teach fundamental mathematical concepts (multiplication, division, GCF) within an ethnomathematics framework. By analyzing game mechanics and observing student engagement, the study demonstrates Congklak's effectiveness in fostering positive attitudes towards mathematics, enhancing problem-solving skills, and promoting deeper conceptual understanding. While previous research has explored Congklak in mathematics education, the novelty of this study lies in its specific focus on analyzing the game's rules to explicitly demonstrate how it embodies and reinforces key mathematical principles. This approach provides a more nuanced understanding of Congklak's pedagogical value and offers a replicable model for integrating other traditional games into mathematics curricula.